2021
DOI: 10.1213/ane.0000000000005399
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Prescriptions by Pain Medicine Physicians in the Medicare Part D Program: A Cross-Sectional Study

Abstract: BACKGROUND: Pain medicine physicians (PMP) are a group of physicians with background training in various primary specialties with interest and expertise in managing chronic pain disorders. Our objective is to analyze prescription drug (PD) claims from the Medicare Part D program associated with PMP to gain insights into patterns, associated costs, and potential cost savings areas. METHODS: The primary data source for Part D claims data is the Centers for Medicare and Medicaid Services (CMS) Chronic Condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Patients suffering from CP usually had higher exposure to analgesics, such as nonsteroidal anti-inflammatory drugs (NSAIDs), opioids, salicylic acid and derivatives (SADs), and anilides. 5,6 Observational research revealed a link between the use of analgesics and a higher risk of cognitive impairment and dementia, 7,8 suggesting a potential role of pain relief drugs in mediating the association between CP and cognitive decline or dementia. A community-based prospective study by Neelamegam et al 9 showed that older adults with long-term opioid use had decreased cognitive performance.…”
mentioning
confidence: 99%
“…Patients suffering from CP usually had higher exposure to analgesics, such as nonsteroidal anti-inflammatory drugs (NSAIDs), opioids, salicylic acid and derivatives (SADs), and anilides. 5,6 Observational research revealed a link between the use of analgesics and a higher risk of cognitive impairment and dementia, 7,8 suggesting a potential role of pain relief drugs in mediating the association between CP and cognitive decline or dementia. A community-based prospective study by Neelamegam et al 9 showed that older adults with long-term opioid use had decreased cognitive performance.…”
mentioning
confidence: 99%